The relationship between nutritional status and meningitis outcomes in children - Hanif Muslim; Astri Pinilih; Nopi Sani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Meningitis is a central nervous system infection with high morbidity and mortality in children. Nutritional status plays a critical role in immune response and may influence clinical outcomes. Purpose: To determine the association between nutritional status and clinical outcomes of pediatric meningitis patients. Method: An analytical observational study with a cross-sectional design was conducted using medical record data of pediatric meningitis patients aged 0–18 years. Statistical analysis was performed using chi-square test and odds ratio (OR). Results: Among 44 patients, 77.3% had poor nutritional status. Mortality rate was 47.7%. A significant association was found between nutritional status and clinical outcomes (p=0.007). Malnourished children had 12.857 times higher risk of death compared to well-nourished children. Conclusion: Nutritional status significantly affects meningitis outcomes in children. Early nutritional assessment and intervention are essential in management strategies.